PENERPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 7 PEMATANG PUDU KECAMATAN MANDAU KABUPATEN BENGKALIS - Yonnita Yonnita; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning social study class III SDN 18 Balai Raja. From 22 Students who achieve KKm just 7 Students (31,81%) while students who didn’t complete 15 students (68,18%) with an average 60,18. The purpose of this research to inprove learning out comes IPS class III SDN 18 Balai Raja. with the application of learning models cooperative Snowball Throwing results obtained by the average value of 60,18 basic score in creased in the first cycle of 18,14% to 71,11 in the second cycle the average value of students also increased by 36,34% to 82,05 on the basic of completeness score IPS Student learning out comes is only 31,81% (finished). After the professor of applied learning model cooperative Snowball Throwing. In the first cycle classical completeness increased 71,11% (not finished), the second cycle of classical completeness obtained are increased to increased 82,05%. Activities of teacher at the first meeting of 58,3% with both categories. The second meeting increased to 79,1% in both categories. In the second cycle increased to 83,3% with the category very well. At a meeting of the second of the second cycle. The activities of teacher increased to 87,5% with the category very well. Activities of students in the first cycle of the fisrt meeting activity students acquire a percentage of 54,16% in both categories. The second meeting of the fisrt cycle to 70,3% inboth categories. At the first meeting of the second cycle of student activity increased to 83,3% with the category very well, and at the second meeting of the second cycleincreased again to 91,6% with the category very well.Key words : Snowbwll Throwing, learning outcomes IPS